(untitled) (Scottish Historical and Archaeological Internet Reports, 2011)
All the evidence for Neolithic activity is presented in this chapter. The timber structure is described under the following headings: terminals, side walls, internal structural elements, internal features and external features, and possible interpretations are presented. There are specialist sections on radiocarbon dates, prehistoric pottery (including a single Iron Age sherd), fired clay, bone and charred plant remains. The discussion considers the evidence for a single structure or separate structures, function and destruction.